2009
DOI: 10.1523/jneurosci.2658-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regionalized Loss of Parvalbumin Interneurons in the Cerebral Cortex of Mice with Deficits in GFRα1 Signaling

Abstract: Inhibitory interneurons are crucially important for cerebral cortex function and behavior. The mechanisms controlling inhibitory interneuron diversification and allocation to distinct cortical areas remain poorly understood. GDNF (glial cell line-derived neurotrophic factor) and its receptor GFR␣1 have been implicated in the development of GABAergic precursors but, because of the early lethality of null mutants, their roles in postnatal maturation and function of cortical interneurons are unknown. "cis-only" m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 37 publications
(67 reference statements)
4
72
1
Order By: Relevance
“…Some of the genes expressed in the PV1 nucleus (listed in Table 1) are known to occur in subclasses of GABAergic neurons. These include: Pitx2 (Skidmore et al, 2008;Waite et al, 2011), Scrt (Marin & Nieto, 2006), Scn1a (Ogiwara et al, 2007;Martin et al, 2010), Gfra1 (Pozas & Ibanez, 2005;Canty et al, 2009), Lynx2 (Dessaud et al, 2006 and Tmem163 (Burré et al, 2007). Of the tested genes, only Lynx2, Slc17a6 and Adcyap1 were expressed exclusively in the glutamatergic neurons of the PV1 nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genes expressed in the PV1 nucleus (listed in Table 1) are known to occur in subclasses of GABAergic neurons. These include: Pitx2 (Skidmore et al, 2008;Waite et al, 2011), Scrt (Marin & Nieto, 2006), Scn1a (Ogiwara et al, 2007;Martin et al, 2010), Gfra1 (Pozas & Ibanez, 2005;Canty et al, 2009), Lynx2 (Dessaud et al, 2006 and Tmem163 (Burré et al, 2007). Of the tested genes, only Lynx2, Slc17a6 and Adcyap1 were expressed exclusively in the glutamatergic neurons of the PV1 nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…GFR␣1 also associates with the neural cell adhesion molecule, NCAM, to mediate the effects of GDNF independently of RET (4 -6). Some of the activities of GDNF can also be mediated by GFR␣1 in the absence of either RET or NCAM, suggesting alternative mechanisms of transmembrane signaling (7,8). A thorough understanding of the molecular mechanisms by which GDNF functions in different contexts will be essential to elucidating its contribution to nervous system development and exploiting its therapeutic potential.…”
mentioning
confidence: 99%
“…The realization that many of these disorders may have a strong developmental component has directed the focus of current research towards the understanding of those signals and mechanisms that control the development of cortical GABAergic interneurons. GDNF has emerged as an important signaling molecule guiding the differentiation and migration of GABAergic neuron precursors in the MGE (Canty et al, 2009;Pozas and Ibáñez, 2005). In addition to defects in cortical PV interneurons, adult 'cis-only' mice also show abnormal social behavior (Canty et al, 2009), suggesting a possible role for GFR1 in human cognitive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons isolated from the MGE of mutant mice lacking GFR1 do not respond to GDNF (Pozas and Ibáñez, 2005), indicating the essential requirement of this receptor subunit. Using a mutant mouse line that circumvents the lethality of the null mutation of Gfra1, herein referred to as 'cis-only mice', we have recently found that GFR1 is required for the correct allocation of parvalbumin (PV) expressing interneurons in the cortex (Canty et al, 2009). Cis-only mice displayed a striking loss of PV interneurons in discrete regions of the cerebral cortex (PV holes) interspersed amongst areas of normal density of PV-positive cells (Canty et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation